2014
DOI: 10.1093/cid/ciu725
|View full text |Cite
|
Sign up to set email alerts
|

A Breath Fungal Secondary Metabolite Signature to Diagnose Invasive Aspergillosis

Abstract: In patients with suspected fungal pneumonia, an Aspergillus secondary metabolite signature in breath can identify individuals with IA. These results provide proof-of-concept that direct detection of exogenous fungal metabolites in breath can be used as a novel, noninvasive, pathogen-specific approach to identifying the precise microbial cause of pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
120
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(129 citation statements)
references
References 36 publications
1
120
0
2
Order By: Relevance
“…For example, 2-aminoacetophenone has been detected in the headspace of Pseudomonas aeruginosa cultures (Bean et al 2012) as well as the breath of cystic fibrosis patients chronically colonized with this organism (Scott-Thomas et al 2010). The compounds α- and β-trans-bergamotene have been detected in the headspace of Aspergillus fumigatus cultures, and also in the breath of patients with invasive aspergillosis (Koo et al 2014). Nicotinic acid has been detected in the headspace of Mycobacterium tuberculosis cultures (Syhre and Chambers 2008) and its methylated derivative, methyl nicotinate, has been detected in the breath of M. tuberculosis infected individuals (Syhre et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, 2-aminoacetophenone has been detected in the headspace of Pseudomonas aeruginosa cultures (Bean et al 2012) as well as the breath of cystic fibrosis patients chronically colonized with this organism (Scott-Thomas et al 2010). The compounds α- and β-trans-bergamotene have been detected in the headspace of Aspergillus fumigatus cultures, and also in the breath of patients with invasive aspergillosis (Koo et al 2014). Nicotinic acid has been detected in the headspace of Mycobacterium tuberculosis cultures (Syhre and Chambers 2008) and its methylated derivative, methyl nicotinate, has been detected in the breath of M. tuberculosis infected individuals (Syhre et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…2-Pentylfuran (2-PF) was detected in the breath of patients with A. fumigatus infection (9). It was shown that A. fumigatus produces farnesene when grown in vitro (10), and the use of terpene volatiles for the detection of IA has recently been proposed (11). However, the spectrum of volatile organic compounds (VOCs) produced by A. fumigatus and their synthesis have been poorly described.…”
mentioning
confidence: 99%
“…This biomarker was demonstrated to be exhaled by patients and to be produced by A. fumigatus in vitro (46,47). Similarly, recent GC-MS and gas chromatography-solidphase microextraction studies of A. fumigatus in vitro and in vivo demonstrated other candidate VOCs for IA, such as monoterpenes and sesquiterpenes (18,48). Last, the current study strengthens the suggestion that eNose technology can detect such a distinct profile of metabolites produced by A. fumigatus in vivo by means of exhaled breath analysis.…”
Section: Discussionmentioning
confidence: 81%
“…Previously, we showed that patients with PCIN and IA have a distinct exhaled breath profile that can be discriminated by an electronic nose (eNose) (17). Very recently, this was confirmed by using gas chromatography-mass spectrometry (GC-MS), demonstrating exhaled metabolite signatures of Aspergillus fumigatus in vitro and IA in vivo (18).…”
mentioning
confidence: 82%